2021
DOI: 10.1016/j.jhin.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Limited implementation of measures to reduce nosocomial spread of COVID-19 in hip-fracture patients in the North West of England

Abstract: Hip fracture patients are vulnerable to the outcomes of COVID-19. We performed a cross-sectional survey to determine measures employed to limit nosocomial spread of COVID-19 in 23 orthopaedic trauma hospitals in North-West England. 19 (87%) hospitals admitted patients to a ward prior to a negative swab, and only 9 (39%) were barrier nursed. Hip fracture patients were operated in non-COVID-19 free theatres in 21 (91%) hospitals. Regular screening of doctors working in trauma and elective areas for COVID-19 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Nevertheless, our results demonstrate substantial variation in PPE use by orthopaedic specialist trainees caring for hip fracture patients in the NW of England during the 2nd surge of the COVID-19 pandemic [2]. This study calls for a significant improvement in the provision of PPE in NW England, given the potentially grave impact of COVID-19 infection in hip fracture patients.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Nevertheless, our results demonstrate substantial variation in PPE use by orthopaedic specialist trainees caring for hip fracture patients in the NW of England during the 2nd surge of the COVID-19 pandemic [2]. This study calls for a significant improvement in the provision of PPE in NW England, given the potentially grave impact of COVID-19 infection in hip fracture patients.…”
Section: Discussionmentioning
confidence: 69%
“…High rates of nosocomial COVID-19 infection have been reported in health-care workers (HCWs) and patients. We recently demonstrated very limited implementation of measures to prevent nosocomial spread during the second surge of the COVID-19 pandemic in orthopaedic units across NW England [2].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study we have shown substantial deficiencies in the measures adopted to limit nosocomial COVID-19 infection in hip fracture patients in hospitals in the North West of England. 30 Public Health England (PHE) published guidelines for hospital care with high, medium and low COVID-19 risk pathways. 31 Acute hip fracture patients would qualify as high risk patients and therefore should be nursed in a single room or specific area until their laboratory test results is known.…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance should ideally be accompanied with other preventive measures and hospitals should be prepared not only for the large influx of community-acquired COVID-19 cases, but also to protect those patients requiring urgent or semi-urgent care, as well as HCWs [ 32 , 33 ]. At the time when the review was conducted, none of the identified HOCI surveillance systems matched the surveillance definition developed by the Centers for Disease Control and Prevention (CDC) in that the results of the surveillance were not provided by a central network [ 34 ].…”
Section: Discussionmentioning
confidence: 99%